Development of rigidity-controlled terpolymer donors for high-performance and mechanically robust organic solar cells. Issue 9 (17th February 2023) - Kim, Jinseck; Kim, Geon-U; Kim, Dong Jun; Lee, Seungjin; Jeong, Dahyun; Seo, Soodeok; Ko, Seo-Jin; Yoon, Sung Cheol; Kim, Taek-Soo; Kim, Bumjoon J.
Abstract : The electro-active third component (BID)-incorporated PM6-B10-based organic solar cell shows a high performance (PCE = 17.2%) and mechanical stretchability (COSavg = 11.4%), outperforming the PM6-based device (PCE = 15.8%, COSavg = 2.0%). Abstract : Organic solar cells (OSCs) are potential power sources for wearable electronic devices. However, the mechanical stretchability of active materials is not yet sufficient; one of the main reasons is the high rigidity of polymer donors (PD s) and the resultant excessive crystalline structures, which makes the active layer mechanically-fragile. In this study, we develop a series of PM6-based terpolymers (PM6-B X ; X = 10–30, X indicates the mole percentage of the third component) in which a bulky electro-active third component, 7, 8-bis(5-hexylthiophen-2-yl)-11 H -benzo[4, 5] imidazo[2, 1- a ]isoindol-11-one (BID), is introduced to reduce the tightness of their molecular packing. As a result, the neat PD film with 10 mol% BID (PM6-B10) exhibits significantly improved mechanical ductility ( i.e., average crack onset strain (COSavg ) of 23.8%) compared to that of the neat PM6 film (COSavg = 14.9%) without a BID unit. In addition, in terms of a blend film, the well-intermixed domains of PM6-B10 and a small molecule acceptor afford OSCs with a high power conversion efficiency (PCE) of 17.2% and mechanical stretchability (COSavg = 11.4%), outperforming the PM6 counterpart (PCE = 15.8%, COSavg = 2.0%). This study suggests important guidelines for the design of efficient PD s for high-performance, stretchable OSCs.